Dexmedetomidine as an anesthetic adjuvant in laparoscopic surgery: An observational study using entropy monitoring - Poonam S Ghodki; Shalini K Thombre; Shalini P Sardesai; Kalpana D Harnagle (Wolters Kluwer Medknow Publications, 2012)
Background: Dexmedetomidine is a highly selective α2 agonist with properties of sedation, analgesia and anxiolysis, making it an ideal anesthetic adjuvant. Using an anesthetic adjuvant that decreases requirement of anesthetics and analgesics may predispose the patient to awareness. We monitored the depth of anesthesia (DOA) using entropy to avoid unwanted awareness under anesthesia. Materials and Methods: 30 patients, American Society of Anesthesiologists grade I and II, aged between 18 to 50 years of either gender undergoing laparoscopic surgeries under general anesthesia were studied. Loading dose infusion of dexmedetomidine was started 1 mcg/kg for 15 minutes and patients were premedicated. Routine induction with propofol and fentanyl was carried out, and maintenance infusion of dexmedetomidine 0.2 mcg/kg/hr was given. Patients were monitored with standard monitoring, and in addition, the DOA was monitored with entropy. Results: A 62.5% reduction (0.75 mg/kg) in the induction dose of propofol was observed, with a 30% less end-tidal concentration of isoflurane requirement for maintenance of anesthesia, while maintaining the adequate DOA. Conclusion: Dexmedetomidine is an effective anesthetic adjuvant that can be safely used in laparoscopy without the fear of awareness under anesthesia.